A new Cyrtodactylus (Squamata: Gekkonidae) from Binh Thuan Province, southern Vietnam - Ostrowski, Sabrina; Le, Minh Duc; Ngo, Hanh Thi; Pham, Cuong The; Phung, Trung My; Nguyen, Truong Quang; Ziegler, Thomas (European Journal of Taxonomy, 2021)
We describe a new species of Cyrtodactylus on the basis of two specimens collected from Ta Kou Nature Reserve, Binh Thuan Province, southern Vietnam. Cyrtodactylus chungi sp. nov. is distinguished from the remaining Indochinese bent-toed geckos by a combination of the following characters: relatively small body size (SVL up to 68.5 mm); a continuous neckband; 5 or 6 irregular transverse dorsal bands; 11 or 12 bands on original tail; keeled tubercles present on dorsum, posterior limbs and tail; 17 or 18 irregular dorsal tubercle rows; 30 or 31 ventral scale rows; ventrolateral skin folds indistinct; an angular series of seven precloacal pores in male and six pitted, enlarged precloacal scales in female, each series separated by a diastema of undifferentiated scales from 4–6 enlarged, poreless femoral scales; median subcaudals slightly enlarged; 17–20 subdigital lamellae under the fourth toe. Based on molecular analyses of the fragment of mitochondrial gene cytochrome c oxidase subunit I (COI), the new species is recovered as the sister taxon to Cyrtodactylus cattienensis s. str. with a genetic divergence of more than 9%. In phylogenetic analyses, the new species is recovered as a member of the Cyrtodactylus irregularis species group.